Structural Health Monitoring of Marine Propellers Using Strain Modal Parameters - Azzi, Rachid; Asma, Farid (International Journal of Integrated Engineering, 2026)
The marine propeller in operation undergoes local defects on the surface and edges of the blades, thus causing vibrations of the propulsion system and a reduction of the propulsion efficiency of the propeller. These local defects develop gradually under the effect of cyclic stresses and lead to the failure of the marine propeller blade by fatigue. In this article, a unique non-destructive approach for structural defect identification in marine propeller blades is presented. The defect identification methods defined by modal strains, such as strain mode shapes changes, strain flexibility changes, and defect index, were used to find and identify single and multiple defects in the marine propeller blade’s structure. The modal strain-related defect indicators were calculated from the strain mode shapes. The strain mode shapes of the marine propeller blade are tri-axial and are calculated along the x, y, and z directions of vibration. In this article, three defect types were considered, with different sizes along the length of the three guide curves starting from the blade base to the free end. The results proved that the proposed defect identification methods defined by modal strains can accurately locate single and multiple defects up to four appearing on the leading edge, the trailing edge, and the propeller blade surface. The magnitude of the defect index at nodes of defective elements is higher (order of 10-2) than the magnitude of strain mode shapes change (order of 10-3), and much higher than the magnitude of strain flexibility change, which is of the order of 10-9. The defect severity quantification on a marine propeller blade is feasible as the magnitudes of the three proposed defect indicators at the nodes of the defective elements are proportional to the severity of the defects.